Pengembangan Media Pembelajaran Gembell (Game Based Learning Berbasis Wordwall) Pada Mata Kuliah Fisika Lanjut - Asiroha Siboro; Kaleb Amaghi Yenusi (Universitas Hamzanwadi, 2025)
Entering the 21st century, technological developments are growing more rapidly, especially in the world of education. With this rapid technological development, all Educators and Education Personnel are required to be able to adapt to developments, mastery and knowledge of technology because technology is a competency that must be mastered to support the improvement of the learning process. The aim of this study is to develop Gembell (Game Based Learning by Wordwall) as an evaluation media that is valid, practical, and effective for 21st-century learning. The research method use is Research and Development (R&D) with as ADDIE model. This research uses observation, interviews, and questionnaires as data collection instruments. Based on the results results, the material validity test score was 89 %, the media validity test score was 87 %, the teacher feasibility test score was 90 %, and the student test score was 95,74 %, received a positif response from the students. From the results of these scores can be concluded that the media for the topic of advanced physics is highly valid, practical, and suitable for use.